Cognitive reserve, modifiable-risk-factor profile and incidence of dementia: results from a longitudinal study of CFAS Wales. (2nd December 2021) - Jia, Feifei; Liu, Fei; Li, Xin; Shi, Xin; Liu, Yvhai; Cao, Fenglin
Abstract: Objectives: Both cognitive reserve and modifiable-risk-factor profiles play a role in dementia incidence. We investigated whether cognitive reserve moderates the risk of dementia attributable to the modifiable-risk-factor profile. Method: We followed 2102 older individuals aged 65+ years recruited from the population-based longitudinal cohort CFAS Wales study, begun in 2011, and the follow-up wave completed in early 2016. Cognitive reserve was measured by combining educational level, occupation complexity, and engagement in social and cognitive activities in later life. Modifiable-risk-factor profile scores were based on depression, diabetes, smoking, physical activity, healthy diet, and drinking. The interactions between cognitive reserve indicators and modifiable-risk-factor profiles were assessed on multiplicative and additive scales. Results: There is an additive interaction between the composite effect of cognitive reserve indicator and modifiable-risk-factor profile on dementia. In those with low cognitive reserve, the risk of dementia in participants with a favorable profile was significantly lower than in those with an unfavorable one (OR = 0.08, 95% CI = 0.02–0.27). Conclusion: Cognitive reserve significantly moderates the association between modifiable-risk-factor profiles and dementia.